Application of Augmented Reality Technology for Human Excretion System as Android-Based Learning Media - Mohamad Kany Legiawan; Dina Agustina (Teknik Informatika Universitas Suryakancana Cianjur, 2021)
The excretion system is a process of removing metabolic waste that is no longer used by the body. These remnants of metabolism in the form of compounds that are toxic (poison) so that if not removed can cause disruption of the function of organs in the body. Organs that play a role in the excretion system are the kidneys, lungs, skin and liver. Kidney is the main component making up the human excretion system, namely urine. The lungs produce residual respiratory processes in the form of gas CO2 (carbon dioxide) and H2O (water vapor). The skin is able to produce residual substances in the form of sweat. The liver produces waste products in the form of bile sap from an overhaul of red blood cells that have been damaged and destroyed in the spleen. Augmented Reality Human Excretion System is an application that can facilitate teachers and class XI MA Tanwiriyyah students in learning about the human excretion system. This application is made based on Android by applying augmented reality technology in its implementation. In this application the teacher and students can see 3D objects and know the process of removing residual substances in the excretory system organs. The design of this application uses the MDLC method and also uses UML diagrams, navigation structures and application interface design.